Analisis Manajemen Hubungan Masyarakat dalam Meningkatkan Partisipasi Orang Tua dan Masyarakat di Sekolah Dasar IT Baitul Insan - Nur Vika Zahara; Halimatussadiah Maulidya Ulfa; Muhammad Kaulan Karima (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
This research was motivated by the importance of public relations management in building cooperation among schools, parents, and communities to support the improvement of educational quality in elementary schools. This study aimed to analyze public relations management in increasing parent and community participation in elementary schools. The research used a qualitative approach with a descriptive research design. Data collection techniques were conducted through interviews, observations, and documentation involving the principal, teachers, parents, and community members as informants. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results showed that public relations management was implemented through direct communication in parent meetings, the use of digital media such as WhatsApp Groups, parental involvement in school activities, and collaboration with the community in supporting educational programs. Parent participation was reflected in mutual cooperation activities, assisting students’ learning, and supporting school programs. The obstacles found included parents’ limited time, low digital literacy among some parents, and the lack of optimal evaluation of school public relations programs. The implications of this study indicate that effective public relations management can increase parent and community involvement in supporting the educational process in elementary schools.